Seasonal Fluctuations of Sympatric Field Murids in Hisar - Saxe, Y; Chandana, S S (Annals of Arid Zone, 2016)
The present paoer reveals a general account of rodents and other animals trapped during trapping schedule in wire-meshed traps (size 35 cm x 17 cm) in three different sub-ecological pockets of Hisar area. Lesser bandicoot rat, Bandicota bengalensis; Indian gerbil, Tatero indico and short-tailed male rat, Nesokia indica were the predominant species of district Hisar, Bhiwani and Rohtak, respectively. Howevcr, desert gerbils, Meriones hllrrianae were trapped only from south western part of this area.